The Common Thread: Diversion in the Jurisprudence of a Century of Juvenile Justice - (:unkn) unknown (My University, 2016)
A central objective of those who created the juvenile court was to protect young delinquents from the destructive punishments of the criminal justice system.This promotion of juvenile court as a diversion from criminal justice is distinct from more ambitious programs of “child saving” intervention because avoiding harm can be achieved even if no efective crime prevention treatmentsare available. This essay shows diversion has been an important motive in juvenilejustice from the beginning, and the dominant purpose of a separate juvenilecourt since In Re Gault in 1967. The past thirty years have been the juvenilecourt’s finest hour as a diversion project; the rate of juvenile incarceration hasbeen stable, while incarceration of young adults has soared.